2017
DOI: 10.1186/s12978-017-0363-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of parents training on parents’ knowledge and attitudes about adolescent sexuality in Accra Metropolis, Ghana

Abstract: Background: Attitudes of parents about discussing sexuality issues with adolescents may or may not be influenced by their level of knowledge on such issues. This study seeks to examine parents' training and its effects on parent knowledge and attitudes about sexuality in Accra Metropolis, Ghana. Methods: This was an intervention study consisting of 145 parents who were recruited through their wards from 12 public junior high schools in Accra Metropolis. Parents were randomized equally into intervention and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
2
22
0
Order By: Relevance
“…This study focused on parents' experiences discussing sexuality topics with their adolescent children. In agreement with previous studies in Ghana [15,26] and in sub-Saharan Africa [22], parents reported talking to their adolescent children on various sexuality topics. Regarding sexual topics discussed with the adolescents, the parents reported that they discussed menstruation, peer pressure, premarital sex, HIV/AIDS, boy/girl relationships, personal hygiene, pregnancy, abstinence, sexually transmitted infections (STIs), abortion, and how to say "no" to forced sex.…”
Section: Parents Discussing Sexuality Topics Withsupporting
confidence: 90%
See 2 more Smart Citations
“…This study focused on parents' experiences discussing sexuality topics with their adolescent children. In agreement with previous studies in Ghana [15,26] and in sub-Saharan Africa [22], parents reported talking to their adolescent children on various sexuality topics. Regarding sexual topics discussed with the adolescents, the parents reported that they discussed menstruation, peer pressure, premarital sex, HIV/AIDS, boy/girl relationships, personal hygiene, pregnancy, abstinence, sexually transmitted infections (STIs), abortion, and how to say "no" to forced sex.…”
Section: Parents Discussing Sexuality Topics Withsupporting
confidence: 90%
“…Other researchers have also reported similar views by parents in different countries [4,5,34,35]. Training parents to talk to their children about sexuality has other benefits like improving their knowledge of sexuality topics, confidence, ability, and comfort to discuss such sensitive topics with their children [26].…”
Section: Informal and Formal Sexuality Educationmentioning
confidence: 62%
See 1 more Smart Citation
“…Parental support for adolescents has also enhanced adolescent pregnancy prevention. This is demonstrated by a study conducted by Baku et al [48] on the effects of training on parents’ knowledge and attitude towards adolescent sexuality; they found that training parents for a relatively short period could positively influence parents’ knowledge and attitudes about adolescent sexuality.…”
Section: Discussionmentioning
confidence: 88%
“…[ 6 7 ] However, in many developing countries, including Iran, sexual and reproductive health has become a challenging issue. [ 8 9 10 11 12 ] In Iran, a qualitative study on the sexual and reproductive health of adolescent girls found that the concept of reproductive health in adolescents is not well understood and is highly controversial. Policymakers and other stakeholders should strive to provide reproductive health services that are consistent with the cultural and religious values of adolescent girls in Iran to overcome the present challenges.…”
Section: Introductionmentioning
confidence: 99%